2017
DOI: 10.1007/s11605-017-3466-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cost Effectiveness of Laparoscopic Pancreatoduodenectomy

Abstract: OBJECTIVE We sought to determine if laparoscopic pancreatoduodenectomy (LPD) is a cost effective alternative to open pancreatoduodenectomy (OPD). METHODS Hospital cost data, discharge disposition, readmission rates, and readmission costs from periampullary cancer patient cohorts of LPD and OPD were compared. The surgical cohorts over a 40 month period were clinically similar, consisting of 52 and 50 patients in the LPD and OPD groups, respectively. RESULTS The total operating room costs were higher in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Anesthesia and operating room costs were significantly higher for LPD compared to OPD in one study, but similar in a recently published study by Gerber et al. . Only Tan et al.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Anesthesia and operating room costs were significantly higher for LPD compared to OPD in one study, but similar in a recently published study by Gerber et al. . Only Tan et al.…”
Section: Resultssupporting
confidence: 79%
“…They are shown in Table . Operative costs were significantly higher for LPD compared to OPD in all four studies that reported on this topic (overall, +$1,372) due to higher costs for surgical equipment . Anesthesia and operating room costs were significantly higher for LPD compared to OPD in one study, but similar in a recently published study by Gerber et al.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations